DEVELOPMENT OF FLIPPING BOOK LEARNING MATERIALS INTEGRATED WITH PROBLEM-BASED LEARNING TO IMPROVE STUDENTS' DIGITAL LITERACY - Delima, Cicci Ima; Rohman, Fatchur; Muntholib, Muntholib; Maasawet, Elsje Theodora (Jurnal Pendidikan Matematika dan IPA, 2024)
Digital literacy is the ability to access, manage, understand, evaluate and create information safely and appropriately. This research aims to produce a valid, practical and effective problem-based learning flipping book instructional material focusing on the diversity of mangrove species, Gonda Mangrove Park, Polewali Mandar to increase student"™s digital literacy. This research is RD and follow the ADDIE instructional design model. The population in this study were X4 SMAN 2 Majene, Sulawesi Barat. The research instrument used pretest-posttest, questionnaires and digital literacy observation sheets. Data analysis through N-Gain Test. The findings obtained from this study indicate a percentage of validity test such as material 100%, learning instruction 81.42%, lesson plan 95.75% and educational practitioner 100%. Practicality test including one-to one trial 83.17%, small group trial 86.90% and field trial 88%, three of them categorized as practical. Based on the N-Gain score, the effectivity of instructional materials shows 0.71, it means the learning materials increasing student"™s digital literacy effectively.